Processed CTD Images from the Ross Sea acquired during the Nathaniel B. Palmer expedition NBP0601 (2005) (IEDA: Marine-Geo Digital Library, 2006)
This data set was acquired with a Sea-Bird SBE-911 CTD during Nathaniel B. Palmer expedition NBP0601 conducted in 2005 (Chief Scientist: Dr. Giacomo DiTullio). These data files are of GIF format and include Temperature, Salinity, Fluorescence, Fluid Chemistry, and Radiation images that have not been processed. Data were acquired as part of the project(s): Interaction of iron, light and CO2 on phytoplankton community dynamics in the Ross Sea, and funding was provided by NSF grant(s): ANT03-38097, ANT03-38157, ANT03-38164, and ANT03-38350.